Sustainable Tourism through Green Event Perspectives in Danang City: Challenges and Solutions - Trinh Thi Thu; Thế Toán Đinh (International Journal of Community Service & Engagement, 2022)
While there has been much research on non-green events in creating massive ecological footprints, including high use of energy, water, food and natural resources, relatively little research has been conducted on the green event’s role in achieving sustainable tourism. The capacity, resources, innovation and engaging a range of key stakeholders, various ways in which events have been considered and operationed as green ones. The current paper sought to explore contemporary challenges to put forward the argument that Danang’s tourism industry acknowledges the importance of the green events. From secondary data sources, the paper concludes with an analysis of future research that needs to be associated with the green event management model to formulate and implement tourism policies in sustainable tourism development.